Motivasi dan Minat Belajar Siswa Kelas XI IPA pada Mata Pelajaran Matematika di Madrasah Aliyah Swasta Al-Falah Tambolaka - Femiyati, Malo; Ludo, Lubur Dorothea Novia; Mulyadi, Making Samuel Rex; Woda, Napu Timotius (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of motivation and interest in learning on the mathematics learning outcomes of Grade XI IPA students at Madrasah Aliyah Swasta Al-Falah Tambolaka. This study uses a descriptive qualitative approach. Data collection techniques were carried out by distributing questionnaires on motivation and interest in learning to students, as well as documentation in the form of mathematics learning outcome scores. The questionnaire data was used to describe the students' level of motivation and interest in learning, while the documentation data was used to observe their mathematics learning outcomes. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing by comparing the students' motivation and interest in learning with their learning outcomes. The results showed that motivation and interest in learning play an important role in increasing student engagement during the mathematics learning process. Students with high motivation and interest in learning showed enthusiasm, focus, active participation, and a better ability to understand the material. Conversely, students with low motivation and interest in learning tended to have difficulty understanding the material, paid less attention to the teacher's explanations, and were not optimally involved in learning activities.